Analysis on Relay Coordination in IEEE 9 bus PV integrated Hybrid Power System using ETAP software: A case study. Issue 1 (June 2021) - Mukherjee, Subhajit; Mandal, Ratan; Ganguly, Arijit; Kumar Paul, Asoke
Abstract: The modern power system of the country like India, there is an important need to design an uninterrupted electrical power system network having adequate security, stability and reliability. In this present paper an IEEE 9-Bus hybrid system is considered for a short circuit analysis and protection relying coordination for designing of overcurrent relaying scheme to operate the relay efficiently and disconnect the fault section from healthy section instantly. It also compares the differences between existing systems with PV connected hybrid system. Now days, when Electrical Power System adopts the Renewable Energy source with existing power source of the network, the main challenge is to design a protection scheme to protect the hybrid system where different intermittent sources make a great impact. To design such a power system the behavior of the existing protection scheme need to be analyzed. In this paper authors simulate an IEEE 9-Bus system using ETAP simulation and analysis is made through Load Flow Study and Short Circuit Analysis. The study reveals that the behavior of the protection system changes with variation of the renewable energy sources integrated with in the bus system. Also set point of the protection relays varies with percentage sharing of the load by PV sources compared to the existing scheme. Observation of the behavior of existing protection system with PV connected hybrid system generates a road map to design an accurate protection scheme for hybrid system.